Frege und die Logik - Kanterian, Edward (Philosophische Rundschau, 2023)
Frege was one of the greatest logicians of all time, and also one of the founding fathers of analytic philosophy. For much of the 20th century, his work tended to be read in abstraction from its historical context. In the last decades, however, there have been more attempts to relate him not only to developments in the mathematics of his time, but also to the philosophical and logical debates preceding and surrounding him, especially also in Jena's academic circles. As several of the books reviewed here demonstrate, this contextualisation has intensified in recent years, not least in German-speaking Frege studies. What is still missing is a reliable intellectual biography.Lothar Kreiser, Gottlob Frege. Leben - Werk - Zeit, Hamburg: Meiner, 2001. XII, 646 S. Gottfried Gabriel/Sven Schlotter, Frege und die kontinentalen Ursprünge der analytischen Philosophie, Münster: mentis, 2017. 251 S. Dale Jacquette, Frege: A Philosophical Biography, Cambridge: Cambridge University Press, 2019. 680 S. Matthias Wille (Hrsg.), Fregesche Variationen. Essays zu Ehren von Christian Thiel, Münster: mentis, 2020. 307 S. Matthias Wille, Gottlob Frege, Begriffsschrift, eine der arithmetischen nachgebildete Formelsprache des reinen Denkens, Berlin: Springer Spektrum, 2018. VIII, 355 S. Tabea Rohr, Freges Begriff der Logik, Münster: mentis, 2020. 211 S.